1978
DOI: 10.1002/mrc.1270110705
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐13 nuclear magnetic resonance spectroscopy of naturally‐occurring substances‐ LVII Triterpenes related to lupane and hopane

Abstract: The -C NMR spectra of lupeol and related triterpenes were recorded and all carbon shifts assigned. Their analysis aided in the shift assignment of the strncturally related hopane-like triterpenes.After early work on some tetracarbocyclic triterpenes2s3 there appeared 13C NMR analyses of a-and pamyrinic pentacarbocyclic substance^.^,^ However, except for a report on two hopanes from an oil shale deposit' and the use of a limited number of friedelin shifts for the interpretation of @effects in transdecalin syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
10

Year Published

1985
1985
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(91 citation statements)
references
References 19 publications
4
77
0
10
Order By: Relevance
“…Elution was carried out using 250-mL fractions of solution varying in concentration from pure hexane to 94% hexane/6% ethyl acetate (v/v%). Twenty-five fractions were collected in this way with 1 appearing in fractions [8][9][10][11][12][13][14][15]. The collected fractions were rechromatographed under similar conditions, yielding 1.3 g of crude compound.…”
Section: Methodsmentioning
confidence: 99%
“…Elution was carried out using 250-mL fractions of solution varying in concentration from pure hexane to 94% hexane/6% ethyl acetate (v/v%). Twenty-five fractions were collected in this way with 1 appearing in fractions [8][9][10][11][12][13][14][15]. The collected fractions were rechromatographed under similar conditions, yielding 1.3 g of crude compound.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of an additional oxymethine signal indicated that 2 is a hydroxylated lupeol derivative. The localization of the hydroxyl group at C-22 of the lupane framework was proposed by comparison with 13 C NMR data (Table 1) of 16-hydroxylupeol 5 and the correlations observed in the long range HETCOR of H-22 (δ 3.68) and C-28 (δ 12.2), C-19 (δ 45.9) and C-18 (δ 45.1) as well as by the carbon shifts observed in the diacetyl derivative (2a) (Table 1). Thus, the NMR spectra of 2a showed a shielding effect at C-21 (Δδ = -3.5 ppm), which is indicative that C-22 bears a hydroxyl group.…”
Section: Ent-3-oxo-labd-8(17)-en-15-oatementioning
confidence: 99%
“…The labd-8(17)-en-15-oic acid (3) was the predominant compound in this extract. From this compound, derivatives (4)(5)(6)(7)(8) were prepared and some of them were submitted to in vitro antibacterial assays.…”
Section: Introductionmentioning
confidence: 99%
“…Estas frações foram cromatografadas separadamente em coluna de sílica gel, monitoradas por cromatografia em camada delgada. A fração hexânica (1 g), eluída continuamente com hexano/acetona na proporção de 95:5 permitiu a obtenção de 29 mg de um sólido branco, identificado como lupeol (2), cujos dados de IV e RMN ( 1 H e 13 C) são idênticos aos da literatura 14 . Sua estrutura foi confirmada por Co-CCD com uma amostra autêntica adquirida comercialmente.…”
Section: Coleta Do Materials E Preparação Dos Extratosunclassified